The Correlation Between the Price of Gold and Monetary Policy: A Case Study of The Chinese Market - Zhong, Jinyu (International Journal of Global Economics and Management, 2024)
Currently, the global economy is confronted with an unstable situation, and due to gold's characteristics as a risk hedge, the gold market has once again garnered significant attention. Many investors are shifting their focus towards gold, particularly in China where it has sparked a gold rush. This study aims to evaluate the relationship between Chinese gold prices, net funding amount, securities amount, money supply, policy interest rates, and exchange rates. By examining the connection between gold and monetary policy, this paper explores the actual role of gold in China's economic landscape. Monthly data from January 2008 to December 2023 were utilized for VAR model analysis. These indicators' channels are interconnected and theoretically impact the country's monetary policy. The conclusion suggests that lowering monetary policy rates in response to easing measures can potentially stimulate inflation and consequently influence upward pressure on the price of gold. Additionally, securities amount negatively affects the price of gold as increasing it serves as China's strategy for curbing inflationary pressures which prevents driving up the price of gold through inflation alone. Other monetary policy indicators also indirectly or directly relate to changes in inflation with potential implications for fluctuations in gold prices. Through these conclusions drawn from our analysis, this research contributes twofold: firstly, by analyzing how changes in monetary policy affect China using its example; and secondly by establishing links between monetary policy decisions and their impact on variations in gold prices. These findings hold relevance for policymakers within central banks or financial institutions alike as well as academia and industry professionals involved with precious metals.